Réactions sociales à la déviance : une étude exploratoire - LeBlanc, Marc; Thi-Hau, Nguyen (Acta Criminologica, 1974)
AbstractSOCIAL REACTION TO DEVIANCE : AN EXPLORATORY STUDYThe object of this exploratory study is to analyse social reactions to deviance by endeavouring to show some of the mechanisms of these re-actions. To do this, we have isolated deviant behaviour from its situational elements in order to study the fluctuations of reactions according to the nature of the deviance, and according to the categories of those reacting to the deviance.The instrument of measurement is a questionnaire which was administered to a random sample for pre-testing. This sample was drawn from the metropolitan region of Montreal. The data analysis is concerned with the degree of generality, consensus, consistency and contingency of reactions in terms of the nature of the deviant behaviour.The results showed the reactions to be surprisingly general. The regularity of the continuum drawn by the indices of contingency and those of strictly punitive consensus was remarkable.This exploratory study gives interested researchers information on crime-deviance continuums and social reactions to deviance. The continuum of social reactions is clearly defined, and this gives us reason to believe it would be possible to introduce an order of importance in the evaluation of social reactions.